A Comparison of the Program Escuelas Promotoras de Paz on Self-Efficacy towards Physical Activity among School Students of Honduras and Nicaragua - Álvarez Bogantes, Carlos (2022)
The objective of the study was to compare the effect of the intervention called Escuelas Promotoras de Paz towards the self-efficacy of students in two schools in Central American countries, Honduras and Nicaragua. The participants in this study were 216 schoolchildren, (n = 108 in each country) between ages 8 and 13 (10.49 ± 0,95 years of age). The self-efficacy questionnaire towards physical activity was administered to the participants (Aedo & Ávila, 2009). In this intervention, the Ecological Model was used based on physical education classes twice a week; active and organized recesses were developed with social support to promote physical activity for students. It was found that Honduran schoolchildren had a worse perception of self-efficacy than Nicaraguan students. It was also evidenced that girls, regardless of their country, presented better self-efficacy than boys, perceiving themselves to be more successful when doing the physical activities included in the intervention. The perceived self-efficacy of boys decreased over the course of the study, while girls remained stable or tended to improve their self-efficacy. Future studies should consider the differentiated response by sex in this variable to generate more effective interventions.